Pancasila's Influence on Student Perspectives Regarding Tolerance and Diversity : A Case Study at Politeknik Bhakti Kartini - Yasin Azhari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
As Indonesia’s foundational ideology, Pancasila promotes national unity by encouraging tolerance and inclusivity among its people. This study explores how students at Politeknik Bhakti Kartini comprehend and apply Pancasila principles in their daily lives, particularly concerning cultural diversity and tolerance. Adopting a qualitative descriptive method, this research analyzes student perspectives through surveys and thematic evaluations. The results suggest that while students possess a solid theoretical grasp of Pancasila, challenges persist in translating these values into practical actions, particularly in fostering inclusivity and countering digital misinformation. This study highlights the need for adaptive teaching methods, interfaith and intercultural discussions, and enhanced digital literacy programs to strengthen students’ application of Pancasila values. By integrating experiential learning and encouraging proactive engagement, higher education institutions can cultivate a more inclusive and tolerant academic environment.